2020
DOI: 10.1038/s41598-020-70449-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pathogenic variants in DNA damage response and repair genes in patients undergoing cancer risk assessment and reporting a personal history of early-onset renal cancer

Abstract: Pathogenic variants (PVs) in multiple genes are known to increase the risk of early-onset renal cancer (eoRC). However, many eoRC patients lack PVs in RC-specific genes; thus, their genetic risk remains undefined. Here, we determine if PVs in DNA damage response and repair (DDRR) genes are enriched in eoRC patients undergoing cancer risk assessment. Retrospective review of de-identified results from 844 eoRC patients, undergoing testing with a multi-gene panel, for a variety of indications, by Ambry Genetics. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 48 publications
4
17
0
1
Order By: Relevance
“…Our overall cohort had a high proportion of patients with advanced RCC. This may account for the higher prevalence of FH and SDH mutations associated with aggressive disease compared to prior germline sequencing studies in RCC [5,7]. We previously reported that the overall frequency of germline mutations was also higher among patients with advanced RCC [8].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Our overall cohort had a high proportion of patients with advanced RCC. This may account for the higher prevalence of FH and SDH mutations associated with aggressive disease compared to prior germline sequencing studies in RCC [5,7]. We previously reported that the overall frequency of germline mutations was also higher among patients with advanced RCC [8].…”
Section: Discussionmentioning
confidence: 83%
“…A study of 190 Chinese patients with RCC diagnosed at the age of 45 yr found that 9.5% had germline pathogenic/likely pathogenic (P/LP) variants, of which two-thirds were in RCC predisposition genes and one-third were in cancer predisposition genes that have not been linked to RCC risk, such as BRCA1/2 [4]. In the USA, another study of 844 patients with RCC diagnosed at the age of 60 yr found germline mutations in 12.8% of patients, but only 3.7% had mutations in RCC predisposition genes [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, 7/229 (3.1%) mutation carriers with germline CHEK2 variants were identified among metastatic clear cell renal cancer patients by Ged and colleagues [ 217 ]. CHEK2 germline mutations were also the most frequent alterations found in 19/844 (2.25%) patients with early onset RCC developed before the age of 60 [ 218 ]. Notably, among these, second primary cancers (breast, thyroid, colon, blood, and ovarian) were reported in 13 (68%) individuals.…”
Section: Germline Chek2 Variantsmentioning
confidence: 99%
“…DNA repair deficiencies lead to a hypermutable state resulting in increased formation of neo-antigens, and may serve as a biomarker of ICI efficacy [78,79]. In RCC, DNA repair gene alterations have been documented at frequencies of approximately 19-25% [80,81], with CHEK2, ATM, and BRCA1, and BRCA2 most commonly implicated [80,82]. Up to 26 DNA repair genes have displayed differential expression in ccRCC compared to benign tissue, six of which were identified as potential prognostic biomarkers (ISG15, RAD51AP1, SFRP2, SLFN11 as high-risk genes; SPATA18, VAV as low risk genes).…”
Section: Dna Repairmentioning
confidence: 99%